МЕТОДИКА ВИКОНАННЯ НАУКОВО-ДОСЛІДНОЇ РОБОТИ ЗА ТЕМОЮ «ГОСПОДАРСЬКО-ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ ЕНЕРГЕТИЧНОЇ БЕЗПЕКИ УКРАЇНИ» - Ashurkov, O.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2015)
The research methodology outlines the content of research projects planned for the topic "Economic and legal support of Ukraine's energy security." The urgency of the research is substantiated, the main goals and tasks are formulated, methods and information base of scientific development are disclosed. The content of works, the order of their carrying out in accordance with the envisaged stages are characterized. The composition of the performers, the terms of implementation and the form of generalization of the main results of the study are presented. REFERENCES